The PRISM Evaluation Resource: Feminist Critical Reflection on Anti-Violence Programs in Rural Areas - Blaney, Elizabeth; Janovicek, Nancy (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
This paper is based on the results of a three-year research collaboration between academics, government, and community organizations from across Atlantic Canada, out of which evolved a resource for critical feminist reflection on violence prevention policies and programs. Through the voices of activists and clients, we describe the components of the PRISM resource for program and policy makers, developed to better respond to violence against girls and women in rural communities.